Opaque indifference and corporate social responsibility: A moral license for offshore BPO? - Wreford, John; Davidson, F.; Pervan, Graham; Penter, Kevan (Springer, 2013)
Offshore Business Process Outsourcing (OBPO) is the delegation of one or more business processes to an external service provider (usually a global in-house centre or a third party). The focus of OBPO research is often the cost benefits of global BPO services. As demands by stakeholders for organisational justification of OBPO decisions and activities increase, reducing resistance to OBPO, particularly where global in-house centres provide services to onshore end-users, requires managing attitudes to OBPO in the community. Improving an organisation’s Social License to Operate relies on the community of stakeholders tacitly approving an organisation’s activities, based on acceptance of organisation’s legitimacy and ethics. The concept of ‘opaque indifference’ (OI) and corporate social responsibility both play a role in improving end-user and stakeholder satisfaction and acceptance of OBPO.